Giant intermuscular lipoma of hip: A case report. (May 2022) - Jia, Yuyan; Wang, Jianyu; Deng, Wei; Han, Jicheng; Dong, Haisi; Leng, Xiangyang
Abstract: Introduction: Lipomas are one of the most common benign tumors, but deep tissue and huge lipomas are rare. Presentation of case: A 59-year-old middle-aged woman was admitted to hospital for right hip mass resection because of numbness and pain in her right lower limb for 6 months. Ultrasound and nuclear magnetic resonance imaging (MRI) showed irregular mass. On the assumption of malignancy, the patient underwent a right hip mass resection and returned to normal with no short-term or long-term response. HE (hematoxylin-eosin) staining of the tumor showed the characteristics of a benign tumor. Discussion: The pathogenesis of myolipoma is not clear, and it may be related to brown adipose tissue. When lipoma is huge, it needs interventional treatment. Complete encapsulated myolipoma can usually be completely removed, with low recurrence possibility and good prognosis. Conclusion: Giant intramuscular lipoma of hip and its clinical manifestations are relatively rare. And the results of ultrasound imaging are similar to those of the surrounding normal adipose tissue. No significant difference was observed by naked eye. In particular, postoperative pathological examination is needed to make a definite diagnosis and differential diagnosis. Clinically, surgical treatment is often used, and the prognosis is good, but recurrence is possible. The following report discusses the experience of one of our patients, with literature review. Highlights: Compared with other lipomas on the body surface, our reported lipomas in the deep tissues are very rare. Lipomas are a common benign tumor, but huge lipomas are rare and may be malignant. After the operation, the lipoma was removed and the symptoms of nerve compression of the patient were obviously relieved.